Solvatochromic Behavior of Substituted 4-(Nitrostyryl)Phenolate Dyes in Pure Solvents and in Binary Solvent Mixtures Composed of Water and Alcohols - Caroli-Rezende, M (Elsevier B.V., 2018)
Several 4-(nitrostyryl)phenolates have been used recently as solvatochromic dyes in the investigation of pure solvents. Changes in their molecular structures allow a comparison of their solvation patterns to be made in different binary solvent mixtures, in an effort to relate structural factors to the preferential solvation (PS) observed in these media. Firstly, the solvatochromism of four of these probes was studied and a reversal in their solvatochromism was verified, which was expected following a comparison with other similar systems previously studied. The solvatochromic behavior of a series of twelve 4-(nitrostyryl)phenolate dyes was then investigated in water-alcohol mixtures. A sigmoid behavior was verified for one of the dyes in ethane-1,2-diol-water mixtures, and the dye was preferentially solvated by water in the alcohol-rich region. For all other mixture compositions a strong synergy was observed, with the PS of the dye molecules occurring through the less polar moiety of the water-alcohol aggregates in the binary mixtures. In addition, synergy was observed for some dyes, with PS occurring through the less polar moiety of the alcohol-water aggregates. For all of the other water-alcohol mixtures, the probes were preferentially solvated by the alcohol cosolvent. In order to quantify these deviations, a PS (or non-ideality) index PSI was proposed. The PSI values obtained correlated well with the hydrogen-bond donating ability of the alcoholic co-solvent, and also with the basicity of the phenolate dyes, and the trends observed were confirmed with data from the literature for two other phenolate dyes. © 2018 Elsevier B.V.